The Rise and fall of the Australian Agricultural Visa: An Analysis of Labor Migration Policies in the Context of Regional Geopolitics - Allan Dharma Saputra (Syntax Corporation Indonesia, 2024)
This article examines how domestic political dynamics and regional geopolitical considerations influenced the rise and fall of Australia's short-lived Agricultural Visa (AAV) program aimed at recruiting workers from ASEAN countries. Employing a qualitative case study approach and drawing on neoliberal economic theory, securitization theory, and complex interdependence theory, the analysis reveals key tensions. The AAV's genesis reflected neoliberal narratives of filling labor shortages, but its demise exemplified concerns over worker exploitation and adverse impacts on local labor standards. The visa also became entangled in Australia's strategic rivalry with China in the Pacific, with labor migration becoming a securitized issue. Crucially, the case exposes challenges of policy coherence, as actions in the security domain strained Australia's ASEAN relationships. The findings underscore the need for holistic approaches balancing economic needs, worker rights, regional diplomacy, and evolving security dynamics when crafting labor migration policies amidst complex global interdependencies. The AAV's failure serves as a cautionary tale about piecemeal, politically expedient migration strategies disconnected from on-the-ground realities.